1989
DOI: 10.1063/1.101980
|View full text |Cite
|
Sign up to set email alerts
|

Scaling law for temporal dispersion of a short electron pulse across a diode in space-charge regime

Abstract: The space-charge phenomenon in the diode of a photoinjector induces simultaneously temporal and spatial dispersions of the electrons burst in pulsed regime. They are higher when the initial pulse duration is shortened. Here, we present the results of temporal dispersion obtained by computer simulation and we give a simple scaling law accounting for it. This law can be used to compare durations of electron pulses at the cathode and anode in any well-defined operation set, in space-charge regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Moreover, it has been suggested that electron emission can be significantly reduced by a space charge effect. [40][41][42][43][44][45][46] Since a large number of electrons are emitted in a short timescale, the negative charge outside the target generates an electric field that prevents electrons from being effectively emitted. Depending on the applied laser fluence, electron emission can be reduced by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been suggested that electron emission can be significantly reduced by a space charge effect. [40][41][42][43][44][45][46] Since a large number of electrons are emitted in a short timescale, the negative charge outside the target generates an electric field that prevents electrons from being effectively emitted. Depending on the applied laser fluence, electron emission can be reduced by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-requisites for such photocathode materials are that they should be rugged and tolerant of relatively poor vacuum (10-7-10-8 mbar), require minimum processing, emit electrons promptly with temporal spread over the irradiating laser pulse of less than a few femtoseconds [3]. They must also be capable of yielding peak current densities exceeding 1 kA cm-* in a pulse length lower than a few picoseconds in spite of the spacecharge effect in the diode [4], have UV incident photonto-electron conversion efficiency > and he able to hold off high fields (2 IO8 V m-') for afew nanoseconds without suffering electrical breakdown. From this point of view, metallic photocathodes are good candidates.…”
Section: Introductionmentioning
confidence: 99%
“…This number is significantly smaller than the 10 12 electrons predicted by the Richardson-Dushman equation, assuming no blockade of electron ejection [39]. We believe that the strong SC effect [32][33][34][35], which is concomitant with the electron emission process, is responsible for this discrepancy. The earliest emitted electrons tend to prevent the remaining hot electrons from being effectively ejected.…”
mentioning
confidence: 65%
“…After intense optical excitation, a large number of electrons are ejected by MPPE and TE. Due to the space-charge (SC) effect [32][33][34][35], the ejected charge cloud undergoes self-expansion, pushing the electrons on the far side farther into the vacuum and the electrons closer to the film back to the film surface. The shadow image and beam deflection measurements have revealed a nearly hemispherical distribution of the ejected charges escaping at an isotropic and constant expansion rate.…”
mentioning
confidence: 99%